2019
DOI: 10.1007/s12571-019-00953-8
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale irrigation scheme governance - poverty nexus: evidence from Ethiopia

Abstract: Irrigated agriculture has been popularized as a key factor to improve crop yields and enhance food security in Africa. However, empirical findings are mixed. This study analyzes determinants of small-scale irrigation adoption and the impact this may have on food security in Ethiopia, where agricultural land is extremely fragmented and densely populated. Data were collected from 240 farmers, and the findings from the survey were triangulated with focus group discussions and key informant interviews. First, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 56 publications
(117 reference statements)
2
13
0
Order By: Relevance
“…Although small-scale irrigation schemes have been promoted in sub-Saharan Africa to ensure food security, less than 5% (640,000 ha) of the agricultural land in Ethiopia is irrigated, which includes 128,000 ha from rainwater harvesting, 383,000 ha from small-scale irrigation, and 129,000 ha from medium and large-scale irrigation [140,141]. Studies on irrigation schemes have shown that much of the perceived water scarcity level is rather attributed to poor water management practices, weak local institutions, unfavorable governance regimes, and financial issues than to the physical scarcity of water [137,142,143] Table 4. Summary of major findings of water harvesting and small-scale irrigation studies in Ethiopia.…”
Section: Water Harvesting and Small-scale Irrigationmentioning
confidence: 99%
“…Although small-scale irrigation schemes have been promoted in sub-Saharan Africa to ensure food security, less than 5% (640,000 ha) of the agricultural land in Ethiopia is irrigated, which includes 128,000 ha from rainwater harvesting, 383,000 ha from small-scale irrigation, and 129,000 ha from medium and large-scale irrigation [140,141]. Studies on irrigation schemes have shown that much of the perceived water scarcity level is rather attributed to poor water management practices, weak local institutions, unfavorable governance regimes, and financial issues than to the physical scarcity of water [137,142,143] Table 4. Summary of major findings of water harvesting and small-scale irrigation studies in Ethiopia.…”
Section: Water Harvesting and Small-scale Irrigationmentioning
confidence: 99%
“…However, little attempt has been made to understand the performance of large and small-scale irrigation user farmers as compared to the nonuser farmers in Ethiopia. Previous studies focused on the difference between irrigation user and non-user farmers in income [11][12][13], quality of life [11,12,14] and the impact of having access to irrigation on poverty [15,16] and food security [17] without considering the differences in the technical efficiency (TE) of smallholder farmers. The results of these studies have shown that irrigation user farmers produce more, earn a better income, have a relatively better life, and are relatively rich and food-secure than the non-user smallholder farmers.…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous switching regression model (ESRM) accounts for observed and unobserved bias by estimating a simultaneous equation model (Lokshin & Sajaia, 2004). The ETRM is nested in ESRM and is widely applied in the analysis of the welfare impact of policies and technology adoption (Adebayo, Bolarin, Oyewale, & Kehinde, 2018; Adego, Simane, & Woldie, 2019; Adela & Aurbacher, 2018; Heckman, Tobias, & Vytlacil, 2003; Mekonnen, 2017). Other relevant studies have applied ESRM to analyse the effect of land‐use changes on water quality (Abildtrup, Garcia, & Kere, 2015), the effect of a large dam on agricultural production (Chen, Hsu, & Wang, 2018), the effect of climate exposure on afforestation (Oyekale & Oyekale, 2019), and the effect of forced displacement on income (Do Yun & Waldorf, 2016).…”
Section: Methodsmentioning
confidence: 99%